Exploring Needs of Academic Writing Course for LMS in the New Normal - Hanna Sundari; Leonard Leonard (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2020)
Along with the university policy for remote learning during the Covid-19 pandemic and the new normal era, learning management system (LMS) become one of various alternative system to handle online learning. However, its application needs to be well-prepared and well-designed. This present study was a need analysis as an initial stage in developing Moodle LMS-based EFL Materials for academic writing course at university. The participants were 67 students from academic writing course. A questionnaire was major instrument to find out the learning needs and context, accompanied by documentation to seek the activities and materials on the existing course. The results show the needs of academic writing course and the proposed EFL materials through Moodle LMS. Student-participants revealed that the course should be able to improve students’ writing skill in developing academic texts through essay development and research article. Moreover, process writing approach and genre-based approach become the most preferable approach for teaching with plenty of sample texts in PDF format. The students-participants also thought that teacher-feedback, individual project-based assessment, and real-time online session or synchronous mode are the best for online learning through LMS. The proposed Moodle LMS-based EFL materials apparently adopts the steps of process genre-based approach and a framework of Bloom’s digital taxonomy.